Performance of glass fibre reinforced epoxy (GRE) composite pipes under various stress ratios, winding angles and ageing conditions - Ragunathan, Prenesh Krishnan (School of Mechatronic Engineering, 2017)
The aim of this research work involves experimental investigation on the behaviour of the glass/epoxy composite pipes under multiaxial stress ratios. The objectives of this research are; to fabricate a portable automated multiaxial pressure test rig and develop a procedure to conduct the automated ultimate elastic wall stress (UEWS) test under five stress ratios; to investigate the effects of winding angles and hydrothermal ageing on the behaviour of GRE pipes under five stress ratios; to construct failure envelope for different winding angles and ageing conditions based on the stress-strain response of GRE pipes subjected to UEWS test under five stress ratios.